Study of Socio-Economic Aspect and Community Perception on The Development of The Agricultural Area Shrimp Ponds in Pasir mendit and Pasir Kadilangu - Kurniawan, Kurniawan; Iskandar, Yusuf; Sarastika, Tiara (West Science Journal Economic and Entrepreneurship, 2023)
Kulon Progo Government plans to make Pasir mendit and Pasir kadilangu areas agro-tourism of shrimp ponds. The success of a regional development program is usually associated with technical problems and socialization. However, the readiness and ability of the community and the positive perception of the community affect the success of regional development programs. This study aims to assess the socio-economic conditions, determine the public perception of agro-tourism shrimp pond development, and determine the factors that affect public perception of agro-tourism shrimp pond development. Primary data were obtained using a survey method with observation and interview techniques. Descriptive-qualitative analyzed the data through frequency tables, cross tables, and images, while quantitative analysis was carried out based on the regression and multiple linear regression results. The results showed that social and economic conditions are pretty good and rising after the development of shrimp pond farming in Pasir mendit and Pasir kadilangu. In this regard, the public perception of agro-tourism development of shrimp farming areas can be pretty high and agreed on the construction of several considerations. The factors that significantly affect the public perception of agro-tourism products are general knowledge about agro-tourism and income levels.